Nurses’ Experiences of Providing Dysphagia Services Through the Internet+Nursing Service Care Model: Qualitative Study - Zhifang Ren; Ling Tong; Shuojin Fu; Shuai Jin; Yanling Wang; Qian Xiao (Journal of Medical Internet Research)
Abstract BackgroundWith China’s aging population and increasing prevalence of chronic diseases, the Internet+Nursing Service has emerged as a new care model, enabling registered nurses from medical institutions to provide home-based care through a web-based application and offline service model. This care model is particularly beneficial for vulnerable populations, such as patients with dysphagia, who face significant risks like malnutrition and aspiration pneumonia. Nurses play a critical role in delivering these services, yet their experiences, challenges, and support needs remain underexplored. Understanding these factors is essential for improving service quality and establishing standardized care guidelines. ObjectiveThis study aims to explore the experiences and challenges of nurses providing the dysphagia-related Internet+Nursing Service, offering insights to guide the standardization and sustainable development of this innovative care model. MethodsA qualitative study was conducted with 18 nurses who had been providing the Internet+Nursing Service for patients with dysphagia for over 6 months. Purposive sampling ensured the selection of participants with relevant expertise. Semistructured interviews were used for data collection, focusing on nurses’ experiences, challenges, and recommendations. Data were analyzed using conventional content analysis, following an inductive approach to identify recurring themes and patterns. ResultsThe analysis revealed 3 key themes: value representation and social impact; nursing resources and staffing; and safety and management support. Nurses emphasized that patient-centered nursing services enhanced their sense of professional fulfillment and helped alleviate pressure on hospital nursing resources. However, challenges such as insufficient time and energy, inadequate manpower, and underexploitation of service potential limited service effectiveness. To ensure sustainability, nurses highlighted the need for standardized service processes, regular experience exchange, and stronger hospital involvement in managing and supporting the Internet+Nursing Service. ConclusionsThis study highlights both the opportunities and challenges of delivering the dysphagia-related Internet+Nursing Service. While nurses acknowledge the value of this care model, addressing staffing shortages, improving training programs, and strengthening regulatory frameworks are essential for optimizing service delivery. Policy makers and health care institutions should develop standardized guidelines and supportive policies to enhance service sustainability and accessibility.